Minimally invasive implantation of a Sapien 3 Ultra Valve in a degenerated tricuspid bioprosthesis. Issue 6 (25th April 2020) - Ranocchi, Federico; Nicolò, Francesca; Russo, Marco; Lio, Antonio; Cammardella, Antonio; Bergonzini, Marcello; Saitto, Guglielmo; Musumeci, Francesco
Abstract: Surgical management of patients affected by structural valve deterioration of bioprostheses in tricuspid valve position represents a challenge. Furthermore, transcatheter valve‐in‐valve implantation (TVIVI) recently emerged as an interesting option in high‐risk surgical patients. When surgery is performed, replacement of the dysfunctional tricuspid bioprosthesis could be a difficult procedure due to the risk of heart rupture during the prosthesis removal. Herein we report the case of a 52‐year‐old female patient in which a transcatheter TVIVI was successfully performed under direct vision as a bailout strategy due to the impossibility of bioprosthesis removal.